Efficacy of targeted therapy in patients with renal cell carcinoma with pre-existing or new bone metastases - Żołnierek, Jakub; Nurzyński, Paweł; Langiewicz, Przemysław; Oborska, Sylwia; Waśko-Grabowska, Anna; Kusztal, Ewa; Obrocka, Beata; Szczylik, Cezary (Contemporary Oncology/Współczesna Onkologia, 2008)
Background: This single-centre retros-pective analysis of data from three randomized studies and two expanded-access studies compared the effect of interferon (IFN)-alpha, sunitinib, and sorafenib on the occurrence and progression of metastatic bone lesions in patients with renal cell carcinoma (RCC). Material and methods: In total, 292 patients were included in the analysis; 107 received sunitinib 50 mg/day in 6-week cycles (Schedule 4/2), 147 received sorafenib 800 mg/day, and 38 received placebo or IFN-alpha 9 MU three times per week. Results: Pre-existing metastatic bone lesions were reported in 82 patients, of which 30 experienced progression. Twenty-three of 210 patients developed new bone lesions during the study. Overall, sunitinib appeared slightly more effective than sorafenib or IFN-alpha at extending mean time to progression of pre-existing bone lesions (p=0.057). Compared with sorafenib, sunitinib significantly decreased formation (p=0.034) and prolonged time to occurrence of new bone lesions (p=0.047). Conclusions: Further evaluation of the effect of these therapies on bone metastases in RCC is warranted.